La letteratura e il linguaggio - Barbero, Carola (Itinerari, 2024)
Analytic philosophy has mostly focused on language, meaning and reference when examining literature. Such an approach, however interesting, is not enough to understand the aesthetic value of literary works. We cannot simply use literature purely for our semantical and ontological analysis, since we should also be able to ask of books what they can give us. By distinguishing literary language from ordinary language, and by focusing on the ‘opacity’ and ‘transparency’ of language itself, the present essay aims to emphasise the specificity of literature.